MONITORING KETAHANAN HIDUP SEMUT HITAM Dolichoderus thoracicus Smith PADA SARANG BUATAN DI TANAMAN KAKAO - Murnawati Murnawati; Annawaty Annawaty; Umrah Umrah (Biology Department, Mathematics and natural science, Tadulako University, 2018)
The Black Ant, Dolichoderus thoracicus Smith have long been recognized as a potential biological control agent in Cocoa plantation. The aims of this study were to determine how long D. thoracicus can survive on artificial nests in cacao plantation and to identify the ant competitor of D. thoracicus. The research conducted in three cocoa plantation i.e. Desa Labuan Panimba, Desa Langaleso, and Desa Pantoloan in Donggala District, Sulawesi Tengah. Artificial nest of D. thoracicus made from bamboo and palm leaves smeared with palm sugar solution and then hung in cocoa trees. The black ant, D. thoracicus can be survived for thirty days in the cacao plantation in Desa Labuan but only one day in Desa Langaleso. The weaver ant (Oecophylla smaragdina) and Philidris sp. were identified as the competitors of D. thoracicus ants inside the artificial nests. Keywords: Dolichoderus thoracicus, artificial nests and ant competitors.